Single‐cell atlas of epithelial and stromal cell heterogeneity by lobe and strain in the mouse prostate. Issue 3 (13th November 2022) - Graham, Mindy K.; Chikarmane, Roshan; Wang, Rulin; Vaghasia, Ajay; Gupta, Anuj; Zheng, Qizhi; Wodu, Bulouere; Pan, Xin; Castagna, Nicole; Liu, Jianyong; Meyers, Jennifer; Skaist, Alyza; et al.
Abstract: Background: Evaluating the complex interplay of cell types in the tissue microenvironment is critical to understanding the origin and progression of diseases in the prostate and potential opportunities for intervention. Mouse models are an essential tool to investigate the molecular and cell‐type‐specific contributions of prostate disease at an organismal level. While there are well‐documented differences in the extent, timing, and nature of disease development in various genetically engineered and exposure‐based mouse models in different mouse strains and prostate lobes within each mouse strain, the underlying molecular phenotypic differences in cell types across mouse strains and prostate lobes are incompletely understood. Methods: In this study, we used single‐cell RNA‐sequencing (scRNA‐seq) methods to assess the single‐cell transcriptomes of 6‐month‐old mouse prostates from two commonly used mouse strains, friend virus B/NIH jackson (FVB/NJ) ( N  = 2) and C57BL/6J ( N  = 3). For each mouse, the lobes of the prostate were dissected (anterior, dorsal, lateral, and ventral), and individual scRNA‐seq libraries were generated. In situ and pathological analyses were used to explore the spatial and anatomical distributions of novel cell types and molecular markers defining these cell types. Results: Data dimensionality reduction and clustering analysis of scRNA‐seq data revealed that basal and luminal cells possessed strain‐specific transcriptomic differences, with luminal cells also displaying marked lobe‐specific differences. Gene set enrichment analysis comparing luminal cells by strain showed enrichment of proto‐Oncogene targets in FVB/NJ mice. Additionally, three rare populations of epithelial cells clustered independently of strain and lobe: one population of luminal cells expressing Foxi1 and components of the vacuolar ATPase proton pump (Atp6v0d2 and Atp6v1g3 ), another population expressing Psca and other stem cell‐associated genes ( Ly6a/Sca‐1, Tacstd2 / Trop‐2 ), and a neuroendocrine population expressing Chga, Chgb, and Syp . In contrast, stromal cell clusters, including fibroblasts, smooth muscle cells, endothelial cells, pericytes, and immune cell types, were conserved across strain and lobe, clustering largely by cell type and not by strain or lobe. One notable exception to this was the identification of two distinct fibroblast populations that we term subglandular fibroblasts and interstitial fibroblasts based on their strikingly distinct spatial distribution in the mouse prostate. Conclusions: Altogether, these data provide a practical reference of the transcriptional profiles of mouse prostate from two commonly used mouse strains and across all four prostate lobes.